Research and choice of computer steganography software for concealment of information transferred through open communication channels - V. M. Alefirenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Criteria for comparative analysis of a computer steganography software are offered. Substantiation and choice of software for researches are carried out. Pilot studies of the chosen software by the offered criteria are conducted and on the basis of the obtained results analysis of the most effective software of a computer steganography for concealment of information is defined.